2009
DOI: 10.1038/embor.2009.242
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear cofactor DOR regulates autophagy in mammalian and Drosophila cells

Abstract: The regulation of autophagy in metazoans is only partly understood, and there is a need to identify the proteins that control this process. The diabetes-and obesity-regulated gene (DOR), a recently reported nuclear cofactor of thyroid hormone receptors, is expressed abundantly in metabolically active tissues such as muscle. Here, we show that DOR shuttles between the nucleus and the cytoplasm, depending on cellular stress conditions, and re-localizes to autophagosomes on autophagy activation. We demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(113 citation statements)
references
References 25 publications
(34 reference statements)
10
103
0
Order By: Relevance
“…During and after phagophore formation, proteins are recruited to the forming autophagosome in a 'retrieve-recycle' manner. The tumor protein 53-induced nuclear protein 2 (TP53INP2; also known as and, hereafter, referred to as DOR) exits the nucleus in response to cellular stress or the activation of autophagy (Nowak et al, 2009;Mauvezin et al, 2010). Cytoplasmic DOR then localizes to autophagosomes where it interacts with the transmembrane protein VMP1 (Nowak et al, 2009).…”
Section: Lir-containing Proteins Associated With Autophagosomes and Omentioning
confidence: 99%
See 1 more Smart Citation
“…During and after phagophore formation, proteins are recruited to the forming autophagosome in a 'retrieve-recycle' manner. The tumor protein 53-induced nuclear protein 2 (TP53INP2; also known as and, hereafter, referred to as DOR) exits the nucleus in response to cellular stress or the activation of autophagy (Nowak et al, 2009;Mauvezin et al, 2010). Cytoplasmic DOR then localizes to autophagosomes where it interacts with the transmembrane protein VMP1 (Nowak et al, 2009).…”
Section: Lir-containing Proteins Associated With Autophagosomes and Omentioning
confidence: 99%
“…Cytoplasmic DOR then localizes to autophagosomes where it interacts with the transmembrane protein VMP1 (Nowak et al, 2009). On autophagosomes, DOR interacts with LC3B through its LIR motif (Sancho et al, 2012), but it does not colocalize with the autolysosome-associated protein LAMP1, indicating that DOR localizes only to early autophagosomes (Mauvezin et al, 2010). Through its interaction with VMP1, DOR presumably acts as a scaffold protein that recruits ATG8 proteins to the autophagosome (Nowak et al, 2009).…”
Section: Lir-containing Proteins Associated With Autophagosomes and Omentioning
confidence: 99%
“…Red and green channels were split in ImageJ and the specific correlation coefficient between cytosolic red and green spots was measured using ICA Plugin (Li et al, 2004;Mauvezin et al, 2010). Pearson's correlation coefficient was quantified from those images (n>15 animals).…”
Section: Image Analysis Colocalization Analysismentioning
confidence: 99%
“…11 It was also shown that TP53INP2 regulates autophagy in Drosophila cells. 12 These findings led us to hypothesize that TP53INP1 also has a role in autophagy.…”
mentioning
confidence: 99%